Kondisi Psikologi Siswa SMK Negeri 5 Pekanbaru dalam Pembelajaran Matematika pada Masa Pandemi Covid-19 - Zulhendri, Zulhendri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2021)
The COVID-19 pandemic has spread since the end of 2019 until now in several regions with differentperiods, including 193 countries that have struggled against Covid attacks, including Indonesia. The Covid-19 pandemic has changed the pattern of education. Initially, the teaching and learning process was carried out face-to-face. But now, the teaching and learning process is carried out remotely by utilizing the internet network, as well as information and communication technology. Therefore, theresearcher intends to find out and describe psychology, namely emotions, beliefs and self-schemes, interests and motivation of junior high school students in online mathematics learning. The research method used is qualitative with the subject of 50 vocational school students of SMKN 5 Pekanbaru. The data collection technique used psychological questionnaires and interviews which were analyzed descriptively. The results showed that the average student psychology was 63%, this means that the overall psychology of students was included in the moderate category, while student psychology is influenced by factors, namely emotion of 65%, self-belief and schema of 59%, interest of 61%, and motivation of 70,25% which overall are included in the moderate category. This psychological analysis can be used by teachers as a teacher design before teaching.